Orientasi kewirausahaan sebagai upaya meningkatkan kinerja pemasaran khususnya UMKM - Evi Permatasari (Pelantar Press, 2022)
There are important things that can increase the productivity of MSMEs, one of which is entrepreneurial orientation. MSMEs in Indonesia which have an entrepreneurial orientation are still low compared to other countries. Characteristics are determined by several factors inherent in the business owner or can be determined by limitations or sizes inherent in the stage of business development. The shortcomings of MSME actors in Indonesia can be caused by a lack of resources such as money, time, knowledge, and expertise. entrepreneurial orientation is very supportive of the performances of business people or MSMEs. The purpose of this study is to find out how entrepreneurial orientation can be an effort to improve marketing performance, especially for MSMEs. This study uses a descriptive narrative method where the main explanation focuses on the results of the analysis and discussion of theories that are in accordance with the research problem. Entrepreneurial orientation has significant and insignificant implications for the marketing performance of SMEs. Based on the results of the research, entrepreneurial orientation has positive implications for marketing performance. Almost all previous studies say that entrepreneurial orientation has a significant effect on marketing performance. However, if you look deeper, some studies still suggest that entrepreneurial orientation does not have positive implications for marketing performance.